Discussion on Technological Developing of Rubber IsolationComponent of Railway Transportation - RONG Ji-gang; HUANG You-jian; CHENG Hai-tao; LIU Jian-xun (机车电传动)
In order to meet anti-vibration technology developing request, future technological development trends of rubber isolation components were discussed in environmental protection, life length, comfort, patent, light-weighting, nicety, function and intelligence.